High-resolution simulation analysis of factors contributing to surface CO2 over central Tokyo metropolitan area - Yousuke Sato; Yutaka Arai; Naoko Saitoh; Qiao Wang; Ryoichi Imasu (Environmental Research Communications)
This study investigated factors contributing to the variation of the surface air CO _2 in summer over the Central Tokyo Metropolitan Area (TMA), one of the most densely populated areas on Earth, by using a meteorological model with a fine horizontal resolution of 500 m. A component for simulating CO _2 in the atmosphere was developed and implemented in the meteorological model. The model was validated by comparison with ground-based and aircraft measurements over the TMA. The evaluation results indicated that the model reproduced the CO _2 concentration and CO _2 daily variation measured by the observations well. The meteorological variation had large effects on the CO _2 variation. The small-scale circulation around TMA contributed to the multi-day variability in the CO _2 concentration over the Central TMA. The CO _2 concentration over the Central TMA tended to be high and low when the northerly and southerly wind was dominant, respectively. The sensitivity experiments clarified the contributions of the ecosystem respiration and photosynthesis, local surface emissions, and large point source emissions to the daily mean concentration of simulated CO _2 over the Central TMA. Our results demonstrate that regional models with fine grid resolution enable us to simulate various processes related to CO _2 variations on a city scale, which is required to refine anthropogenic emissions from urban areas.